Ludvig Holberg og oplysningstidens lærde republik - Olesen, Brian Kjær (Temp - tidsskrift for historie, 2024)
This article explores the relationship between Ludvig Holberg and the Enlightenment republic of letters. The article has two principal aims: first, to shed light on how we can understand Holberg’s intellectual biography within the context of the republic of letters; second, to examine how Holberg’s life and work may be used to illuminate central aspects of the cultural and intellectual history of this republic. Beginning with Holberg’s early European travels, the article examines the place of the republic of letters in Holberg’s intellectual self-perception and the ways in which he constructed various learned personas.